Implementasi Prinsip Good Governance Dalam Pelayanan E-Ktp Dan Kartu Keluarga Di Kecamatan Benda Kota Tangerang - Siti Rafa; Irvan Arif Kurniawan; Muhammad Ibrahim Rantau (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The purpose of this research is to know the implementation of the principles of good governance in the service of E-KTP and Family Cards in Benda District, Tangerang City, Benda District in the E-KTP and Family Card services. To obtain data in this study, the method used is a qualitative research method. The data collection techniques are observation, interviews and documentation. The results of this study indicate that the Implementation of Good Governance Principles in E-KTP and Family Card Services in Benda District, Tangerang City has not gone well, there are still some things that are still not appropriate, such as the existence of services that prioritize people who have positions and kinship , as well as service employees who still serve with unfriendly looks. The results of this study found that the implementation of the principle of Good Governance in the E-KTP and Family Card services was not in accordance with the principles of Good Governance because there was still injustice in providing services by prioritizing one's position and when performing services if people who had families working there the service would be faster. , but behind that there are several principles of Good Governance that have been in accordance with such as Participation, Rule of Law, Transparency, Responsiveness, Consensus Oriented, Effectiveness and Efficient, Accountability, Strategic Vision.